Reference Trajectory Optimization Under Constrained Predictive Control - Lam, David K.; Baker, Rhoda; Le Swartz, Christopher (Canadian journal of chemical engineering, 2007)
Chemical process systems often need to respond to frequently changing product demands. This motivates the determination of optimal transitions, subject to specification and operational constraints. However, direct implementation of optimal input trajectories would, in general, result in offset in the presence of disturbances and plant/model mismatch. This paper considers reference trajectory optimization of processes controlled by constrained model predictive control (MPC). Consideration of the closed‐loop dynamics of the MPC‐controlled process in the reference trajectory optimization results in a multi‐level optimization problem. A solution strategy is applied in which the MPC quadratic programming subproblems are replaced by their Karush‐Kuhn‐Tucker optimality conditions, resulting in a single‐level mathematical program with complementarity constraints (MPCC). The performance of the method is illustrated through application to two case studies, the second of which considers economically optimal grade transitions in a polymerization process. Les systèmes de procédés chimiques doivent souvent répondre à des changements de production fréquents. Ceci motive la détermination de transitions optimales, soumises à des contraintes de spécification et de fonctionnement. Toutefois, l'implantation directe de trajectoires d'entrée optimales entraîne, en général, un décalage en présence de perturbations et d'une incompatibilité installation/modèle. Cet article porte sur l'optimisation des trajectoires pour des procédés contrôlés par le contrôle prédictif par modèle contraint (MPC). Le fait de considérer la dynamique en boucle fermée du procédé contrôlé par MPC dans l'optimisation des trajectoires de référence cause un problème d'optimisation à plusieurs niveaux. Une stratégie de solution est appliquée dans laquelle les sous‐problèmes de programmation quadratique du MPC sont remplacés par des conditions d'optimalité de Karush‐Kuhn‐Tucker. On obtient ainsi un programme mathématique à niveau unique associé à des contraintes de complémentarité (MPCC). La performance de la méthode est illustrée par l'application de deux études de cas, le second considérant les transitions de grade optimales en termes économiques dans un procédé de polymérisation.